A Case of Male Goltz Syndrome - Bhaswati Ghoshal; Subhrajit Lahiri; Debabrata Nandi (Case Reports in Pediatrics)
We present the case of a boy with a clinical diagnosis of Goltz syndrome (focal dermal hypoplasia), a rare genodermatosis characterized by widespread dysplasia of mesodermal and ectodermal tissues. A 9-year-old male patient with Goltz syndrome presented with typical skin lesions along with progressive dimness of vision and mental retardation since birth. It is inherited in an X-linked dominant fashion and is normally lethal in male patients, and so very few male patients, like the index case, have been reported.